Production of N-acyl Homoserine Lactones and Virulence Factors of Waterborne Aeromonas hydrophila - Chu, Weihua (Springer-Verlag, 2013)
Aeromonads are inhabitants of aquatic ecosystems and are described as being involved in intestinal disturbances and other infections. The purpose of this study was to investigate the production of N-acyl-homoserine lactone (AHL) signal molecules and some virulence factors, including hemolysins, proteases, extracellular nucleases production and cytotoxicity by waterborne Aeromonas hydrophila. A total of 24 strains isolated from fresh-water or diseased fish were used in the study. The majority A.hydrophila strains produce two AHL molecules (21/24), one is N-butanoyl homoserine lactone (BHL), and the other is N-hexanoyl homoserine lactone (HHL) according to thin-layer chromatography analysis. Among the virulence factors tested, more than 83 % of the isolates produced β haemolysin when inoculated on sheep blood agar, only 50 % of the isolates displayed DNase activity, 75 % of the isolates shown proteolytic activity on skimmed milk plate, and cytotoxic activity was detected in 20 of 24 of the isolates. The strains producing AHLs possessed one or more virulence factors. In conclusion, the production of quorum sensing signal molecules is common among the strains that we examined, and there seems to some relationships between quorum sensing signal production and virulence factors in A. hydrophila.